Optimalisasi Penjualan Produk UMKM Melalui Pelatihan Digital Marketing dan Desain Kemasan Inovatif di Desa Semaya: Pengabdian - Naelis Ardyadiva Putri; Andi Yulianto; Bambang Irawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program was aimed at improving the sales performance of MSME products in Semaya Village by providing training on digital marketing and the development of creative packaging designs. One of the main challenges faced by micro-entrepreneurs in the village was the lack of understanding of how to utilize information technology for promotional purposes, as well as limited innovation in packaging design, which resulted in low product competitiveness in the market. The program was designed using a participatory approach that actively involved 25 MSME actors from various business sectors. A series of activities were carried out, including educational sessions, interactive training, hands-on practice in using social media and online marketplaces, and the creation of attractive packaging designs that meet modern market standards.The outcomes of the program indicated significant improvement in participants’ skills, such as the ability to create business accounts on digital platforms, develop more structured promotional content strategies, and produce packaging designs that are informative, functional, and visually appealing. In addition to acquiring technical skills, the participants also began to recognize the importance of brand development and the role of product visual quality as strategies to expand market reach and increase sales value.